Beyond self-reports: serum cotinine reveals sex-and age-related differences of smoking on all-cause and disease-specific mortality - Jiang, Qi; Junjun, Liu; Wang, Xiaochuan; Luo, Li; He, Gaoyan; Wu, Xiaojuan; Min, Qian; Long, Ying; Wenjun, Wang; Zhu, Tao; Yao, Yu (Frontiers in Public Health, 2025)
BackgroundIt is well-known that sex and age play critical roles in smoking-related diseases and mortality. However, quantification of the extent of smoking requires self-reports in these studies, which may yield only partially accurate results. This study investigated sex-and age-related differences in the association between smoking and all-cause, cardiovascular disease, and cancer mortality by measuring serum cotinine levels.MethodsParticipants aged 20–85 years from the US National Health and Nutrition Examination Survey (1999–2018) were included. All-cause and disease-specific mortality data were obtained from publicly available user-linked mortality files. Multivariate Cox regression was performed to identify serum cotinine as an independent risk factor of mortality. Subgroup and interaction analyses were performed to investigate these sex and age differences. Smooth curve fitting was conducted to discover potential nonlinear relationships and threshold saturation effects.ResultsSex was significantly associated with all-cause and cancer mortality. Threshold saturation effects were observed in all-cause mortality among both males and females, cancer mortality among females, and cardiovascular disease mortality among males. Age markedly associated with all-cause and cardiovascular disease mortality. Threshold saturation effects were found in cardiovascular disease mortality among younger adults and cancer mortality among the all-age population.ConclusionThese findings suggest that there are threshold saturation effects between smoking and mortality, and sex and age differences in smoking-related mortality are inconsistent in different diseases.